PENERAPAN EVIDANCE BASED NURSING ALIH BARING DAN PEMBALURAN MINYAK ZAITUN DALAM MENCEGAH DAN MENGURANGI LUKA ULKUS DEKUBITUS PADA PASIEN DI RUANG ICU - Novitasari (2022)
The ICU is a critical care room, where a person needs total and comprehensive care, and patients with decreased consciousness often experience decreased mobility and physical activity, which results in prolonged pressure on the patient and can cause pressure sores to form. Decubitus wounds are wounds that are often found on the skin with prominent bony parts such as the sacrum, back, head, heels, which are caused by long-lasting pressure due to mobilization, friction between the body surface and the mattress, or caused by several other factors. Decubitus sores can be prevented by giving bedsores every 2 hours and keeping the skin moisturized with lotions or oils such as olive oil. In this study, the aim of this study was to determine the effectiveness of the combination of bed transfer and olive oil application in patients in the ICU. The assessment in this study used the Braden scale to measure the risk of decubitus ulcers and NPUAP to assess the wound and skin condition. The results of this study were obtained after the application of the intervention for 4 days, there were no pressure ulcers in the patient after the 12th day of treatment in the ICU and the skin became more moist.